2013
DOI: 10.1074/jbc.m112.389627
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Phosphoprotein Binds Annexin 2 and Is Involved in Calcium Transport in Rat Kidney Ureteric Bud Cells

Abstract: Background: Dentin phosphoprotein (DPP), responsible for tooth mineralization, is also present in nonmineralizing tissues like kidney, lung, and salivary glands. Results: DPP binds annexin 2 and 6 and plays a role in calcium influx in rat ureteric bud cells. Conclusion: DPP plays different roles in mineralizing and nonmineralizing tissues. Significance: This is the first report showing a possible function for DPP in nonmineralizing tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…DSPP is an evolutionary younger member of the acidic secretory calcium-binding phosphoprotein gene family (7). The two major DSPP cleaved functional units, DSP and DPP, are highly acidic, with human DPP presenting a very low isoelectric point of 2.84 and high calcium affinity (7,8). It is therefore conceivable that DSPP serves as a buffer protein in ER calcium homeostasis with a similar functional role to other calcium-dependent proteins: Calnexin, calreticulin and GRP78 (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSPP is an evolutionary younger member of the acidic secretory calcium-binding phosphoprotein gene family (7). The two major DSPP cleaved functional units, DSP and DPP, are highly acidic, with human DPP presenting a very low isoelectric point of 2.84 and high calcium affinity (7,8). It is therefore conceivable that DSPP serves as a buffer protein in ER calcium homeostasis with a similar functional role to other calcium-dependent proteins: Calnexin, calreticulin and GRP78 (64).…”
Section: Discussionmentioning
confidence: 99%
“…DSP occupies the N-terminal domain and presents a Cys205 (the only cysteine in DSPP) domain (6,7). C-terminal DPP possesses 165 Asp-Ser-Ser sequence motifs, has a low isoelectric point of 2.84 and exhibits high calcium affinity (7,8). The short DGP fragment is sandwiched between the N-terminal DSP and the C-terminal DPP.…”
Section: Introductionmentioning
confidence: 99%
“…Delay in the maturation of the nephrons was reflected by overall smaller size of the metanephros and less polarized epithelial layers in the nephrons (50). More recently we have shown that in the rat ureteric bud cell line, DPP is localized on the cell membrane where it is associated with annexin 2 (51). When these cells were treated with anti-DPP antibodies the influx of calcium into the cells was reduced by 40%, implying that in non-mineralizing tissues, DPP may play a role in calcium transport (51).…”
Section: Introductionmentioning
confidence: 99%
“…The Dspp gene is known to be primarily expressed in odontoblasts and, to a lesser extent, in osteoblasts [7] , [8] . Dspp is also expressed in other tissues such as the salivary glands, lungs, and kidneys [9] [11] . Functional analyses in genetically altered mouse models mainly elucidated the function of DSPP as an inducer of mineralization in the extracellular matrix [12] [14] .…”
Section: Introductionmentioning
confidence: 99%